Quality of Work Life with Nurse Organizational Commitment During the Covid-19 Pandemic Period - Era Pratiwi; Mega Marindrawati Rochka Rochka; A. Awaliya Anwar (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Health workers, especially nurses, play an important role in health services, especially during the covid-19 pandemic, both in the form of providing health care and treatment, so they are considered the main foundation. The research objective was to determine the relationship between quality of work life (QWL) and nurse organizational commitment during the covid-19 pandemic at Makassar City Hospital. This type of research was quantitative research with a cross sectional study approach. The sample in this study were nurses who served at the Makassar City Hospital Inpatient Installation. The data collection method was carried out by interviewing using a questionnaire. The results of the study in this study were that nurses who had a good level of QWL at most were with high organizational commitment, namely as many as 32 people (80,0%) while nurses who had an adequate level of QWL, the most were with low organizational commitment, namely as many as 24 people (72,7%). The results of the analysis using the Chi-Square Test obtained a value of p=0,000, which means that there was a relationship between the quality of work life and the organizational commitment of nurses during the Covid-19 pandemic at the Makassar City Hospital. From the results of the study, it was concluded that there was a relationship between QWL and the organizational commitment of nurses during the covid-19 pandemic at Makassar City Hospital.